ответ:1-oе фото
1)x²-2x-35 2)3x²+16x+5 3)x²-13x+40
x²-2x-35=0 3x²+16x+5=0 x²-13x+40=0
D=4+4*35=144 D=256-4*3*5=196 D=169-4*40=9
x1=(2+12):2=7 x1=(-16+14):6=5 x1=(13+3):2=8
x2=(2-12):2=-5 x2=(-16-14):6=0,3333333 x2=(13-3):2=5
4)6x²+x-1
6x²+x-1=0
D=1+4*6*1=25
x1=(-1+5):12=0,3333333
x2=(-1-5):12=-0,5
ответ: 21/16
Объяснение:
1) b(n)=b1*q^(n-1).
Отсюда, b3=b1*(q^2)
b3=1/16, q=1/4, а значит 1/16=b1*((1/4)^2); 1/16=b1*(1/16), отсюда b1=1
2) S(n)=(b1(q^(n-1)-1))/(q-1)
Отсюда S4=(1*(((1/4)^3)-1))/(1/4-1)=(1/64-1)/(1/4-1)=(63/64)/(3/4)=21/16